Influencing Factors on the Postoperative Patient Functional Status at the Meuraxa Regional General Hospital, Banda Aceh - Ritawati, Ritawati; Nurhayati, Nurhayati; Baharuddin, Baharuddin; Muna, Ulfa; Faisal, T. Iskandar; Khaira, Nuswatul (Poltekita: Jurnal Ilmu Kesehatan, 2024)
After surgery, the patient will experience pain which can change the role and function in carrying out activities of daily living (ADL), the patient will depend on his family or other people for his life. The aim is to determine the factors that influence the functional status of post-operative patients at the Meuraxa Regional General Hospital, Banda Aceh. Method: using analytical observational methods with a cross-sectional approach. The population in this study were all post-operative care patients at Meuraxa Regional Hospital. The sample in this study were patients treated on the second day after minor surgery at Meuraxa Regional Hospital Banda Aceh with a sample size of 43 respondents. The statistical test uses the chi-square test with a significant level (α=0.05). The research results show that the factors that influence postoperative functional status are pain and fall-efficacy factors (p<0.05), while the age factor is not significantly correlated (p>0.05). Conclusion: Pain and fall-efficacy factors are the most important factors influencing postoperative active status and are statistically significant.